ECCB's 2005/2006 annual report : presentation - Venner, K. Dwight (ECCB BasseterreKN, 2006)
Reports on the performance of the Bank. Seeks to enable persons throughout the region to have a better understanding of what the Bank does to ensure that the currency is strong and stable.